2018
DOI: 10.1111/ssqu.12563
|View full text |Cite
|
Sign up to set email alerts
|

Political Leaning and Coverage Sentiment: Are Conservative Newspapers More Negative Toward Women?*

Abstract: Objectives. This article examines whether newspapers' political leaning affects coverage tone for individuals in the news and whether the gender of the person covered affects this relationship. Methods. I analyze sentiment data on millions of person-names from more than 200 major American newspapers between the years 2004 and 2009, juxtaposing them with various measurements for the political leaning of these newspapers. Results. Results show mixed support for the idea that political leaning in the media affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
6
1
2
Order By: Relevance
“…We then tested the ability of this system to identify negative and positive events in the lives of several celebrities. We found that sudden shifts in sentiment indeed corresponded with these events, providing support for the validity of the sentiment measure (see also Shor, 2018).…”
Section: Dependent Variable: Newspaper Sentimentsupporting
confidence: 71%
“…We then tested the ability of this system to identify negative and positive events in the lives of several celebrities. We found that sudden shifts in sentiment indeed corresponded with these events, providing support for the validity of the sentiment measure (see also Shor, 2018).…”
Section: Dependent Variable: Newspaper Sentimentsupporting
confidence: 71%
“…The data is free, publicly available, and considered as an important source of information for researchers from different disciplines. Many previous studies collected information from ACS and leveraged with Twitter data to analyze sentiment of the people in the arena of public health [30] , urban spaces [40] , politics [41] , [42] , disasters management [43] , racial conflicts [32] , [44] , and gender disparity [45] . Thus, linking Twitter data with Coronavirus data is a common practice among the researchers to evaluate the impacts of socioeconomic and demographic characteristics on the sentiments of the people towards a subject of interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies also point out that the political slant of the media may condition the portrayal of women politicians depending on the party to which they belong. For Shor (2019), there is mild support for the idea that relatively liberal newspapers are more likely to cover women's issues in a positive light. Indeed, the political affiliation of the media outlet may be one of the factors that helps to understand the differences between media coverage of male and female politicians, but Shor et al (2014) found that both conservative and liberal newspapers are more likely to cover men.…”
Section: Theoretical Frameworkmentioning
confidence: 99%